Mean Platelet Volume in Hyperthyroid Toxic Adenoma Patients after Radioactive 131I Treatment. (23rd November 2015) - Simsek, Eda; Timur, Ozge; Carlioglu, Ayse; Arikan Durmaz, Senay; Demirci, Munir; Sevimli, Hakan
Abstract : This study demonstrates that mean platelet volume (MPV) levels decrease after radioiodine (RAI) ablation therapy in hyperthyroid patients. Regarding the fact that large platelets are hemostatically more active, we suggest that hyperthyroid patients are at risk of cardiovascular disease despite all other cardiovascular risk factors. After RAI ablation therapy as MPV levels return to normal, cardiovascular risk for hyperthyroid patients reduces.